The Impact of Interpersonal Communication and Self-Esteem on Teacher Turnover - Ahmad, Masduki; Rochimah, Heni (FKIP Universitas Lampung, 2021)
The Impact of Interpersonal Communication and Self-Esteem on Teacher Turnover. Objectives: The purpose of this study is to see how interpersonal communication and self-esteem play a role in the turnover of civil servant teachers in Public Elementary School, Sub-District Setiabudi, Jakarta’s Special Capital District. Methods: This study used a basic random selection technique to select 126 civil servant teachers as a sample. To investigate the contribution and influence of the independent factors on the dependent variable, this study used multiple linear regression models. Findings: After conducting the research, several findings were obtained, include: (1) Interpersonal communication has a negative and significant effect on teacher turnover with a significance value of 0.000; (2) Self-esteem has a negative and significant effect on teacher turnover with a significance value of 0.000; (3) Interpersonal communication and self-esteem have an effect on teacher turnover with a determination coefficient value of 0.944. Conclusion: Well-maintained communication between colleagues and build self-esteem in teachers will make a teacher more receptive to himself, improve his performance and reduce teacher’s turnover. Keywords: interpersonal communication, self-esteem, turnoverDOI: http://dx.doi.org/10.23960/jpp.v11.i2.202104